REVENUE ANALYSIS OF BOAR’S SPERM AT BATURITI ARTIFICIAL INSEMINATION CENTER - i K. B. A., Utama; Sumardani, N. L. G.; Mariani, N. P. (Jurnal Peternakan Tropika; Vol 7 No 1 (2019): Vol. 7 Isssues 1 (2019); January - April 2019, 2019)
Baturiti Artificial Insemination Center is one of the centers that produce boar sperm which is very beneficial for the wider community. This business has a very good opportunity, many local people buy boar sperm that is used for Artificial Isememination (B). However, during the course of this business the Baturiti Artificial Insemination Center has not yet made an income analysis calculation. So there is no known profit calculation obtained every month. Then an analysis of business income is needed so that it can be seen as feasible or not feasible to run this boar sperm business. Business feasibility analysis is carried out by analyzing non-financial aspects and financial aspects. Non-financial aspects consist of market aspects and environmental aspects. While the analysis of financial aspects carried out includes calculation of profit and RC ratio. The results of the feasibility analysis of the boar sperm business resulted in the loss of losses from the Baturiti Artificial Insemination Center with a loss of Rp -3,809,700 and RC ratio of 0.623, due to expensive feed prices and selling prices very cheap semen, so it needs to be suggested to increase the selling price of boar sperm. Keywords : pork, boar sperm, technical implementation, feasibility analysis